2009
DOI: 10.1007/s11606-009-1073-y
|View full text |Cite
|
Sign up to set email alerts
|

Index to Predict 5-Year Mortality of Community-Dwelling Adults Aged 65 and Older Using Data from the National Health Interview Survey

Abstract: BACKGROUND: Prognostic information is becoming increasingly important for clinical decision-making.OBJECTIVE: To develop and validate an index to predict 5-year mortality among community-dwelling older adults. DESIGN AND PARTICIPANTS:A total of 24,115 individuals aged >65 who responded to the 1997-2000 National Health Interview Survey (NHIS) with follow-up through 31 December 2002 from the National Death Index; 16,077 were randomly selected for the development cohort and 8,038 for the validation cohort.MEASURE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
172
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(191 citation statements)
references
References 26 publications
7
172
0
6
Order By: Relevance
“…The results of our analyses suggest that the model should perform well in other similarly defined populations. The predictive ability of our model is comparable to other studies of older people living in the community (Lee et al 2006;Schonberg et al 2009). …”
Section: Discussionsupporting
confidence: 82%
“…The results of our analyses suggest that the model should perform well in other similarly defined populations. The predictive ability of our model is comparable to other studies of older people living in the community (Lee et al 2006;Schonberg et al 2009). …”
Section: Discussionsupporting
confidence: 82%
“…Previous mortality prediction models were all developed using data from a single study and mostly from the United States and Europe (7-9,13,39-42) and therefore have limited generalizability in other populations (18). We found that the best set of predictors were age, comorbidities, lifestyle factors, and functional status, similar to previous models developed for community-dwelling older adults (7)(8)(9)13,40). In addition, although we included data from 16 countries with widely different mortality rates, our model showed similar discrimination to previous single-study models that had C statistics from 0.69 to 0.83 and less than 10% points difference between observed and predicted risk of mortality across deciles of risk (15).…”
Section: Discussionsupporting
confidence: 68%
“…In addition, participants in all cohorts were asked whether they had "heart disease," whereas in MHAS they were asked about "heart attack," and the frequency of vigorous physical activity were different between HRS, MHAS, and SABE (≥3 times/week), and ELSA and SHARE (≥1 time/week). We also did not have consistent measures of other potential predictors of mortality, such as number of recent hospitalizations (8) and size of the participant's social network (42) across the five cohorts. Moreover, cohorts lost up to 36% of their participants during follow-up, and this may have biased our results if loss to follow-up is associated both with the included predictors and with mortality (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 We focused on validated predictors of mortality in community-dwelling adults who were older adults [13][14][15] or had heart failure. [16][17][18][19] Predictors of the benefit outcome were age (years), gender, smoking status (never, ever, and current), history of diabetes mellitus, left ventricular ejection fraction (continuous), cardiothoracic ratio (continuous), pulse (b min À1 ), diuretic use, serum creatinine (mg/dl), serum sodium (mg/dl), history of chronic obstructive pulmonary disease, and history of stroke.…”
Section: Analytic Methodsmentioning
confidence: 99%